2021
DOI: 10.1186/s12936-021-03625-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of Plasmodium falciparum isolates from Melka-Werer, North East Ethiopia based on the merozoite surface protein-2 (msp-2) gene as a molecular marker

Abstract: Background The characterization of parasite populations circulating in malaria endemic areas is necessary to evaluate the success of ongoing interventions and malaria control strategies. This study was designed to investigate the genetic diversity of Plasmodium falciparum isolates from the semi-arid area in North East Ethiopia, using the highly polymorphic merozoite surface protein-2 (msp2) gene as a molecular marker. Methods Dried blood spot isola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
7
8
3
Order By: Relevance
“…Although the number of genotypes might have be underestimated due to the limitation of the techniques. Fragment size polymorphism described in this study is nearly comparable with the previous report from Republic of Congo [28], Nigeria [29], Sudan [17], and northeastern Ethiopia [30]. Other reports from Congo Brazzaville [31], north western Ethiopia [32] shown the predominance of IC/3D7 allelic family.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the number of genotypes might have be underestimated due to the limitation of the techniques. Fragment size polymorphism described in this study is nearly comparable with the previous report from Republic of Congo [28], Nigeria [29], Sudan [17], and northeastern Ethiopia [30]. Other reports from Congo Brazzaville [31], north western Ethiopia [32] shown the predominance of IC/3D7 allelic family.…”
Section: Discussionsupporting
confidence: 89%
“…This nding is lower than the previous report from southwestern Ethiopia [33] northwesten Ethiopia [32], Sudan [17], Cameroon [34], and Nigeria [35]. And somewhat higher than the previous report from north eastern Ethiopia [30], and Ghana [36]. The variation in multi-clonal infection and multiplicity of infection could be due to the overall prevalence of infection in the population and the age of the individual [37].…”
Section: Discussioncontrasting
confidence: 59%
“…Amplification and gel-electrophoresis of msp-2 alleles in the study revealed 113 and 102 fragments for 3D7 and FC27 genotypes, respectively. Thus, mean MOI could be estimated by dividing the total number of gel fragments detected in the msp-2 gene by the total number of positive samples in the same marker [ 28 , 29 ], which indicates the average number of genotypes per infected subject.…”
Section: Methodsmentioning
confidence: 99%
“…has been related to the ability of parasites to adapt adequately to their hosts through the selection of advantageous traits, such as antigenic variability that allows them to evade the immune response, as well as the emergence of mutations responsible for resistance to antimalarials [3][4][5][6][7]. Genetically diverse populations of Plasmodium are common in regions with high transmission patterns, such as sub-Saharan Africa and some Southeast Asian countries [8][9][10][11][12], but as the incidence of malaria declines, the parasite's genetic diversity is expected to decline as well [13,14]. Central America is considered a region of moderate to low malaria transmission, and studies on the genetic diversity of Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%